Outcomes and Treatment Strategies for Autoimmunity and Hyperinflammation in Patients with RAG Deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (ELSEVIER SCIENCE BV, 2019)
BACKGROUND: Although autoimmunity and hyperinflammation secondary to recombination activating gene (RAG) deficiency have been associated with delayed diagnosis and even death, our current understanding is limited primarily to small case series. OBJECTIVE: Understand the frequency, severity, and treatment responsiveness of autoimmunity and hyperinflammation in RAG deficiency. METHODS: In reviewing the literature and our own database, we identified 85 patients with RAG deficiency, reported between 2001 and 2016, and compiled the largest case series to date of 63 patients with prominent autoimmune and/or hyperinflammatory pathology. RESULTS: Diagnosis of RAG deficiency was delayed a median of 5 years from the first clinical signs of immune dysregulation. Most patients (55.6%) presented with more than 1 autoimmune or hyperinflammatory complication, with the most common etiologies being cytopenias (84.1%), granulomas (23.8%), and inflammatory skin disorders (19.0%). Infections, including live viral vaccinations, closely preceded the onset of autoimmunity in 28.6% of cases. Autoimmune cytopenias had early onset (median, 1.9, 2.1, and 2.6 years for autoimmune hemolytic anemia, immune thrombocytopenia, and autoimmune neutropenia, respectively) and were refractory to intravenous immunoglobulin, steroids, and rituximab in most cases (64.7%, 73.7%, and 71.4% for autoimmune hemolytic anemia, immune thrombocytopenia, and autoimmune neutropenia, respectively). Evans syndrome specifically was associated with lack of response to first-line therapy. Treatment-refractory autoimmunity/ hyperinflammation prompted hematopoietic stem cell transplantation in 20 patients. CONCLUSIONS: Autoimmunity/hyperinflammation can be a presenting sign of RAG deficiency and should prompt further evaluation. Multilineage cytopenias are often refractory to immunosuppressive treatment and may require hematopoietic cell transplantation for definitive management. (C) 2019 The Authors. Published by Elsevier Inc. on behalf of the American Academy of Allergy, Asthma & Immunology.
Keywords: Recombination activating gene (RAG); Severe combined immunodeficiency (SCID); Immune dysregulation; Autoimmune cytopenias; Hematopoietic stem cell transplantation (HSCT); SEVERE COMBINED IMMUNODEFICIENCY; RECOMBINATION ACTIVITY; GRANULOMATOUS-DISEASE; CLINICAL PHENOTYPES; VACCINE-STRAIN; OMENN SYNDROME; MUTATIONS; CYTOPENIAS; RITUXIMAB; GENE